Many unhappy returns one man's quest to turn around the most unpopular organization in America - Rossotti, Charles O. (Boston Harvard Business School Press, 2005)
In 1997, the Internal Revenue Service was a much-maligned public agency mired in unprecedented scandal and crisis. [UNK] Servicing 132 million individual and 6 million business taxpayers, the IRS has by far the largest number of customers in the country. And for years, it also had the lowest approval rating. The power of this story is that if the IRS was turned around so dramatically, so can any other large organization. [UNK] Provides a fresh and informative perspective. Conveys the hopeful message that real, ongoing change is possible at the IRS - an outcome that affects every taxpayer. [UNK] Well-written narrative that directly addresses taxpayers' biggest gripes, and suggests a solution. [UNK] There is a potential market among IRS employees, which number about 100,000.
Includes bibliographical references (p. 317-330) and index.
Keywords: United States. Internal Revenue Service